Retrospective Survey of Dog and Cat Endoparasites in Ireland: Antigen Detection - Theo de Waal; Sandra Aungier; Amanda Lawlor; Troy Goddu; Matthew Jones; Donald Szlosek (Animals, 2022)
Endoparasites of dogs and cats, play an important role in both veterinary medicine and public health. Untreated and stray dogs and cats, in particular, play an important role in contaminating the environment with important zoonotic parasites. Thus, the aim of this study was to estimate the prevalence of intestinal parasites in stray dogs and cats using highly sensitive and specific copro-antigen tests. Archive faecal samples from previous surveys conducted between 2016–2019 from dogs (n = 789) and cats (n = 241) were included in this study. The IDEXX Fecal Dx™ antigen panel was used for the detection of Toxocara, hookworms, Trichuris and the SNAP™ Giardia antigen assay was used for the detection of Giardia infection. Giardia duodenalis was the most common parasite (26%, n = 205) detected in the dogs, followed by ascarids (17.6%, n = 139) and hookworms (5.3%, n = 42). Trichuris vulpis was only detected in 1 dog. Ascarids (23.2%, n = 56) was the most common parasite detected in the cats, followed by Giardia (12.9%, n = 31) and hookworms (n = 7, 2.9%). No whipworms were detected in cats. Overall, there was little difference in the positivity between sexes in both dogs and cats. However, in terms of age, adolescent dogs (<3 years) and kittens (<1 year) had the highest parasite prevalence overall, with G. duodenalis and ascarids being the most prevalent. This study shows a high prevalence of parasite infection in untreated and stray dogs and cats in the greater Dublin area in Ireland. Since they live in synanthropic conditions and can roam over vast distances they can contaminate public areas and pose a risk to both humans and owned pets that utilise these spaces. It is therefore important to raise public awareness and increase the knowledge on zoonotic parasites.